PENAFSIRAN MAKNA LAGU TRADISIONAL BATAK TOBA ANDUNG “SAUR MATUA MAHO INANG” (ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE) - Julyo Armando Hugo; Ilona Situmeang (Universitas Bunda Mulia, 2016)
The purpose of this study to determine the interpretation of the meaning contained in the lyrics of the song